L-arginine and aged garlic extract for the prevention of migraine: a study protocol for a randomised, double-blind, placebo-controlled, phase-II trial (LARGE trial). - Chaliha, Devahuti; Vaccarezza, Mauro; Corti, Emily; Takechi, Ryusuke; Dhaliwal, Satvinder; Drummond, Peter; Visser, Eric; Chen, Fred; Charng, Jason; Lam, Virginie; Mamo, John (BioMed Central, 2023)
Background